PENGARUH LINGKUNGAN KERJA FLEKSIBEL DAN PENGEMBANGAN KARIR TERHADAP PENINGKATAN KUALITAS KERJA GENERASI Z DI DESA WARU SIDOARJO - Rosul, M; Ruliff, Dian Edgina; Rahmadani, Syavira Natania; Kusmayati, Nindya Kartika (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This study aims to analyze the influence of flexible work environment and career development on the quality of work of Generation Z. Generation Z has unique characteristics that affect the way they work and develop in the organization. Researchers use quantitative methods with a correlation approach consisting of two independent variables (X¹) flexible work environment (X²) career development and dependent variables (Y) quality of work of generation Z. The quality of work of generation Z in Waru Village, Sidoarjo is the population in this study. Respondents in this study were 61 and the data processing process used SPSS. The results of this study can be concluded that variables X1 (flexible work environment) and X2 (career development) affect Y (improving the quality of work of generation z), where variable (X1) flexible work environment has a positive effect on variable (Y) quality of work of generation z, and for variable (X2) career development also has a positive effect on variable (Y) quality of work of generation z.